Notes on the genus Iracema Pérez-Miles, 2000 with the first description of the male of I. horrida (Schmidt, 1994) (Araneae: Theraphosidae) - Bertani, Rogério; Carla-Da-Silva, Silvia (Zootaxa, 2003)
The formerly unknown male of Paraphysa horrida is described and the species transferred to the genus Iracema. This genus is rediagnosed and can be recognized by having the combination of the following characters: type IV of urticating hairs, bulb resting in a ventral distal excavation of the male palpal tibia, male metatarsus I touching both branches of tibial spur when flexed, labium with less than 20 labial cuspules, and presence of many spiniform setae on the prolateral and retrolateral sides of maxillae and coxae I-IV.